Re-assessment of recent (2008–2013) surface mass balance over Dome Argus, Antarctica. Issue 1 (1st January 2016) - Ding, Minghu; Xiao, Cunde; Yang, Yuande; Wang, Yetang; Li, Chuanjin; Yuan, Naiming; Shi, Guitao; Sun, Weijun; Ming, Jing
Abstract : At Dome Argus, East Antarctica, the surface mass balance (SMB) from 2008 to 2013 was evaluated using 49 stakes installed across a 30×30 km area. Spatial analysis showed that at least 12 and 20 stakes are needed to obtain reliable estimates of SMB at local scales (a few hundred square metres) and regional scales (tens of square kilometres), respectively. The estimated annual mean SMB was 22.9±5.9 kg m −2 yr −1, including a net loss by sublimation of −2.22±0.02 kg m −2 yr −1 and a mass gain by deposition of 1.37±0.01 kg m −2 yr −1 . Therefore, ca. 14.3% of precipitation was modified after deposition, which should be considered when interpreting snow or ice core records produced by future drilling projects. The surface snow density and SMB in the western portion of Dome Argus are higher than in other areas, and these differences are likely related to the katabatic wind, which is strengthened by topography in this sector. A new digital elevation model (DEM) of Dome Argus was generated, confirming that both peaks of the dome can be considered as the summit of the East Antarctic Ice Sheet. Findings from this study should be valuable for validating SMB estimates obtained from regional climate models and DEMs established using remote-sensing data.